Carbonate alteration of ophiolitic rocks in the Arabian–Nubian Shield of Egypt: sources and compositions of the carbonating fluid and implications for the formation of Au deposits. Issue 4 (12th March 2017) - Boskabadi, Arman; Pitcairn, Iain K.; Broman, Curt; Boyce, Adrian; Teagle, Damon A. H.; Cooper, Matthew J.; Azer, Mokhles K.; Stern, Robert J.; Mohamed, Fathy H.; Majka, Jaroslaw
ABSTRACT: Ultramafic portions of ophiolitic fragments in the Arabian–Nubian Shield (ANS) show pervasive carbonate alteration forming various degrees of carbonated serpentinites and listvenitic rocks. Notwithstanding the extent of the alteration, little is known about the processes that caused it, the source of the CO2 or the conditions of alteration. This study investigates the mineralogy, stable (O, C) and radiogenic (Sr) isotope composition, and geochemistry of suites of variably carbonate altered ultramafics from the Meatiq area of the Central Eastern Desert (CED) of Egypt. The samples investigated include least-altered lizardite (Lz) serpentinites, antigorite (Atg) serpentinites and listvenitic rocks with associated carbonate and quartz veins. The C, O and Sr isotopes of the vein samples cluster between −8.1‰ and −6.8‰ for δ 13 C, +6.4‰ and +10.5‰ for δ 18 O, and 87 Sr/ 86 Sr of 0.7028–0.70344, and plot within the depleted mantle compositional field. The serpentinites isotopic compositions plot on a mixing trend between the depleted-mantle and sedimentary carbonate fields. The carbonate veins contain abundant carbonic (CO2 ±CH4 ±N2 ) and aqueous-carbonic (H2 O-NaCl-CO2 ±CH4 ±N2 ) low salinity fluid, with trapping conditions of 270–300°C and 0.7–1.1 kbar. The serpentinites are enriched in Au, As, S and other fluid-mobile elements relative to primitive and depleted mantle. The extensively carbonated Atg-serpentinites contain significantly lower concentrations of these elements than the Lz-serpentinites suggesting that they were depleted during carbonate alteration. Fluid inclusion and stable isotope compositions of Au deposits in the CED are similar to those from the carbonate veins investigated in the study and we suggest that carbonation of ANS ophiolitic rocks due to influx of mantle-derived CO2 -bearing fluids caused break down of Au-bearing minerals such as pentlandite, releasing Au and S to the hydrothermal fluids that later formed the Au-deposits. This is the first time that gold has been observed to be remobilized from rocks during the lizardite–antigorite transition.